Crucial for Modern Sector Development? The Role of Exports and Institutions in Developing Countries - Rainer Grundmann; Thomas Gries (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Over the past decades there has been ample evidence that a manufacturing sector plays an important role in overall development. In East Asia, recent job creation in industry has lifted large parts of the population to higher income levels. However, while this connection is well supported by anecdotal evidence as well as empirical and theoretical research, there is less evidence on what exactly supports modern sector development. With cross-country time-series data for 75 developing countries we analyze whether international trade and institutions, both the subject of much discus- sion in the general development debate, play a special role in manufacturing sector growth. Our estimation results, produced using an instrumental approach that is less susceptible to endogeneity issues, show that indeed both exports and institutions are vital for a manufacturing sector. Our results also provide interesting insights into the role of natural resources and official development aid.
Keywords: O14; C23; F15; 330